PENGARUH KETIDAKAMANAN KERJA DAN STRES KERJA TERHADAP TURNOVER INTENTION PADA SENSE SUNSET HOTEL SEMINYAK - Surya Negara, Kadek Adi; Dewi, I Gusti Ayu Manuati (E-Jurnal Manajemen, 2017)
T he purpose of this study is to determine the effect of job insecurity and job stress on employee turnover intention. The population in this study were all employees of Sense Sunset Hotel Seminyak which amounted to 110 people while the samples taken in this study were 86 respondents. The method of determining the sample in this study using proportional random sampling. The data was collected by distributing questionnaires using a 5-point Likert scale to measure 15 question items. The analysis technique used is multiple linear regression analysis. The result of the analysis shows that job insecurity and work stress have positive and significant effect on turnover intention. In order to reduce the turnover rate of the company it is advisable to reduce the level of job insecurity and job stress felt by employees.